Project leadership: skills, behaviours, knowledge and values - Coleman, Sarah; Bourne, Mike (Association for Project Management (APM), 2018)
This research has sought to draw out project leadership competences from the perspective of practising project leaders, aspiring project leaders, heads of profession, project sponsors and clients. The aim of this research report is to help focus, develop and refine our understanding of project leadership so we can support continued capability building for project professionals and their organisations. To compile this report, the authors Sarah Coleman and Professor Mike Bourne conducted in-depth interviews with 38 individuals across five multinational organisations (BAE Systems, IQVIA, Jacobs, Shell and Siemens). These organisations were chosen because of their reliance on complex projects for the delivery of strategy and performance, and the individuals for their substantial knowledge and experience of project delivery, and their range of perspectives. The interviewees held and had experience of a wide variety of roles, from the aspiring leaders delivering smaller projects to the most experienced project leaders (responsible for £1bn+ budget major, complex projects), heads of profession, project sponsors and clients. Together, these individuals have over 500 years of project experience.